Pengembangan Aplikasi E-Learning dengan Fitur Penilaian Otomatis pada SMA Manda Elu - Diana Renda; Andreas Ariyanto Rangga; Emirensiana Dappa Ege (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The application and utilization of technology in various fields is evidence that the development of technology is currently growing rapidly in the field. The field of education is one field that is not free from this development, as evidenced by the emergence of the concept of learning (E-learning). Electronic learning can be abbreviated as